2020
DOI: 10.1007/s11125-020-09492-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the opportunity to design a more mindful approach to learning

Abstract: The industry of modern schooling leads to surface learning of exaggeratedly voluminous curricula and excessively high-stakes assessments that instrumentalize the pursuit of knowledge. In order to return to a more mindful, authentic, and humanly paced approach, disruption from the present model is needed. Paradoxically, the COVID-19 pandemic might be the catalyst that will bring this about.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 3 publications
1
16
0
2
Order By: Relevance
“…He sees the crisis as an opportunity for positive change, although he also sees the risks of the proliferation of technology without good pedagogy being developed in parallel with it. According to Hughes (2020), pandemic pedagogy has forced educators to concentrate on the very core of teaching in their subject area. As Robinson (2020, p. 7) states, we need to think carefully 'what kind of normal do we want to go back to?'…”
Section: Discussionmentioning
confidence: 99%
“…He sees the crisis as an opportunity for positive change, although he also sees the risks of the proliferation of technology without good pedagogy being developed in parallel with it. According to Hughes (2020), pandemic pedagogy has forced educators to concentrate on the very core of teaching in their subject area. As Robinson (2020, p. 7) states, we need to think carefully 'what kind of normal do we want to go back to?'…”
Section: Discussionmentioning
confidence: 99%
“…This is an opportunity to escape some of the content-heavy assessment and process that has turned many schools into highly competitive knowledge instrumentals. By concentrating on deep learning and life-worthy knowledge rather than surface learning and test-worthy knowledge, future approaches will move closer to a holistic and enduring goal of education: to gently sow the seeds of lifelong learning for the public good (Hughes, 2020).…”
Section: Prospectsmentioning
confidence: 99%
“…Like others, we have found that the situation of the pandemic is a subject that enters naturally into the conversation, either directly (e.g., by teachers’ and student-teachers’ desires to debrief with one another after their day with students, masks, visors, and restricted movement and materials) or indirectly (as teachers gravitate toward creating thematic units on anxiety, worries, and wellness, or wish to critically revisit and improve their pandemic practices) (Hughes Henry and Kushnick 2020 ). Mindful of students’ accumulated time online and onscreen, we have tailored contact time in class to intervals that do not exceed two hours (Hughes 2020 ). We continue our practices of breaking into small groups (using Zoom breakout rooms), which tend to be smaller than before (e.g., three rather than six students) so as to reach for greater intimacy.…”
Section: Conclusion: Pandemic Teachingmentioning
confidence: 99%